REVERSE TAKOTSUBO CARDIOMYOPATHY FOLLOWING A CASE OF SUSPECTED MENINGOENCEPHALITIS AND LITERATURE REVIEW - Shams, Pirbhat; Intisar Ahmed; Aamir Hameed Khan (Journal of Ayub Medical College Abbottabad, 2021)
Reverse Takotsubo cardiomyopathy is a rare variant of stress cardiomyopathy. A 22-year-old male presented with altered mentation and fever. He was intubated due to low Glasgow Coma Scale. CT head plain showed diffuse cerebral oedema. Patient had raised troponin-I and echocardiogram revealed reduced ejection fraction with hyperdynamic apical segments and akinetic basal to mid segments suggestive of reverse Takotsubo cardiomyopathy (rTCM). Association of rTCM with neuropsychiatric disorders such as intracranial/epidural haemorrhages and anorexia nervosa has been defined. However, it is rare to have rTCM with meningoencephalitis.